Implementation and scaling of climate-smart financing solutions in Kenya's sorghum value chain. Post-investment report - Wamicwe, Peter; Njoroge, Paul; Derenoncourt, Ena; Newman, Richard; Grosjean, Godefroy; Mufti, Samaa; Girvetz, Evan; Bonilla, Osana (2024)
The Kenya Cooperative Development and Investment Program (KCDIP) Sorghum Value Chain Project, implemented under the AICCRA initiative, is transforming the resilience and financial viability of smallholder sorghum farmers in Meru County, Kenya. By introducing an innovative bundled finance model, the project integrates input financing, insurance, and mechanization services, reducing climate risks while unlocking private sector investment. At its core, the initiative focuses on stabilizing farmer cash flows, improving access to finance, and catalyzing private sector engagement. Through strategic partnerships with Shalem Investments, Family Bank, DigiFarm, Kuza Biashara, and ACRE Africa, the project ensures that smallholder farmers receive tailored financial solutions, training, and risk mitigation strategies. In its first phase, 569 farmers received training on Climate-Smart Agriculture (CSA) practices, while 334 accessed financing from a pre-approved USD 520,800 credit line, leveraging concessional funding at a 4:1 mobilization ratio. Despite challenges such as climate variability, market constraints, and operational hurdles, the project successfully implemented a dual de-risking strategy, combining pest and disease management with parametric insurance, which prevented a 3.35% default rate. The use of trainers-of-trainers (ToTs) overseeing a network of 42,500 farmers highlights the scalability and long-term potential of this approach. Building on these successes, the October 2024 pilot is set to integrate improved risk management, enhanced private sector financing mechanisms, and irrigation solutions to strengthen year-round sorghum production. This initiative demonstrates a replicable, finance-driven model for resilience, positioning smallholder farmers at the center of climate adaptation, economic stability, and food security.